2019
DOI: 10.2196/preprints.16634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Explaining Differences in the Acceptability of 99DOTS, a Cell Phone–Based Strategy for Monitoring Adherence to Tuberculosis Medications: Qualitative Study of Patients and Health Care Providers (Preprint)

Abstract: BACKGROUND 99DOTS is a cellphone-based strategy for monitoring tuberculosis (TB) medication adherence that has been rolled out to more than 150,000 patients in India’s public health sector. A considerable proportion of patients stop using this monitoring approach during TB therapy. OBJECTIVE We aimed to understand reasons for variability in the acceptance and use of 99DOTS by TB patients and h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thomas et al reported similar findings among HCWs at government-run TB centers in India. 24 Stigma related to taking TB medication contributed to lower opportunity scores, reflecting the known impact of stigma on TB care. 25 In addition to stigma, barriers to the feasibility of implementing DATs included technical issues with phones, network connectivity, and issues with the two DAT platforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas et al reported similar findings among HCWs at government-run TB centers in India. 24 Stigma related to taking TB medication contributed to lower opportunity scores, reflecting the known impact of stigma on TB care. 25 In addition to stigma, barriers to the feasibility of implementing DATs included technical issues with phones, network connectivity, and issues with the two DAT platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar technical barriers have been reported previously in China, India, Peru, and sub-Saharan Africa. 24,[26][27][28][29] Our analysis had some limitations. First, surveys were administered only to a subset of people with TB in each project.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal engagement with DATs-which may result in under-reporting of true medication adherence (i.e., reduced sensitivity, reduced NPV)-can be influenced by limited access to mobile networks and technology, shared cellphone use among multiple household members, and inadequate education on the purpose and appropriate use of the DAT. (40)(41)(42)(43) With substantial under-reporting of medication adherence, healthcare providers may have difficulty identifying people who are truly experiencing nonadherence, be unable to routinely reach out to all people with reported nonadherence (e.g., via phone calls or home visits) (44), and may begin to ignore digital adherence data due to its limited performance (42,44).…”
Section: Discussion (1126 Words Including Conclusion)mentioning
confidence: 99%
“…First, consistent with findings from clinical trials [20,180,181], non-adherence to TB medications was independently associated with increased risk of unfavorable treatment outcomes (Gap 4) [81,84,93,97,98,121] and TB recurrence (Gap 5) [158] across multiple Indian studies, which suggests that adherence is a mediator of outcomes in programmatic care. However, measuring TB medication adherence in routine care is challenging, with recent studies from India showing that 99DOTS (a digital adherence technology used in the NTEP) and patient self-report have suboptimal accuracy [182][183][184]. Use of novel approaches for detecting nonadherence, such as urine isoniazid testing [29,185], may facilitate early identification of patients at risk for poor outcomes, so that they can be provided with additional support.…”
Section: Findings Specific To Each Care Cascade Gapmentioning
confidence: 99%